2016
DOI: 10.1080/09593330.2016.1193225
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable conversion of agriculture wastes into activated carbons: energy balance and arsenic removal from water

Abstract: The aims of this study are to investigate the production of activated carbons (AC) from Senegal agricultural wastes such as cashew shells, millet stalks and rice husks and to implement them in adsorption processes devoted to arsenic (V) removal. AC were produced by a direct physical activation with water steam without other chemicals. This production of AC has also led to co-products (gas and bio-oil) which have been characterized in terms of physical, chemical and thermodynamical properties for energy recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The X m and K values calculated from the slope and intercept of the plots are given in Table 3. The sorption energy was calculated from the following mathematical expression: (21) The values of sorption energy (E) in the range 8 -16 kJ mol -1 indicate chemisorption (ion exchange mechanism) while E values below 8 kJ mol -1 represent physisorption [43]. In the present study, sorption energy was found to be 10 kJ mol -1 , which indicates that anion exchange mechanism is responsible for the sorption of arsenite onto the surface of Fe-UTAC.…”
Section: Dubinin-radushkevich (D-r) Modelmentioning
confidence: 68%
See 1 more Smart Citation
“…The X m and K values calculated from the slope and intercept of the plots are given in Table 3. The sorption energy was calculated from the following mathematical expression: (21) The values of sorption energy (E) in the range 8 -16 kJ mol -1 indicate chemisorption (ion exchange mechanism) while E values below 8 kJ mol -1 represent physisorption [43]. In the present study, sorption energy was found to be 10 kJ mol -1 , which indicates that anion exchange mechanism is responsible for the sorption of arsenite onto the surface of Fe-UTAC.…”
Section: Dubinin-radushkevich (D-r) Modelmentioning
confidence: 68%
“…A variety of raw materials, namely pistachio-nut shell, guava seeds, peanut hulls, coconut shell, apricot stone, date pits, peach stone, coffee bean husks, chestnut wood, grape seed, corn cob, oat hulls, olive stone, rice husks and sugarcane bagasse have been exploited by researchers for the production of activated carbon [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a number of researchers investigated As(V) and As(III) removal from water using different adsorbent materials and methods (Liu et al, 2020), such as activated carbon (Dieme et al, 2017;Hashim et al, 2019;Kalaruban et al, 2019), zeolite (Meher et al, 2016;Soni and Shukla, 2019), biochar (Niazi et al, 2018b;Singh and Mohan, 2020;Tabassum et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, recovered biomolecules from agricultural waste may present a wide range of applications in the food industry, like natural additives, to improve the organoleptic properties of food or even to formulate functional foods [28][29][30]. Livestock, paper, construction, fuels, fiber, bio-compounds, colorants [38][39][40] Abbreviations: mhL: million hectoliters; mT: million tons.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%